2002
DOI: 10.1063/1.1464652
|View full text |Cite
|
Sign up to set email alerts
|

TaC as a diffusion barrier between Si and Cu

Abstract: The reaction mechanisms and related microstructures in the Si/TaC/Cu metallization system have been studied experimentally and theoretically by utilizing ternary Si-Ta-C and Ta-C-Cu phase diagrams as well as activity diagrams calculated at 800°C. With the help of sheet resistance measurements, Rutherford backscattering spectrometry, x-ray diffraction, scanning electron microscopy, and transmission electron microscopy, the metallization structure with the 70 nm thick TaC barrier layer was observed to fail compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 29 publications
3
28
0
1
Order By: Relevance
“…The sluggish diffusion is also far more pronounced with such a high number of elements, especially at a low deposition temperature, due to the confusion principle [22] and the increased packing density [23]. Finally, the large atomic size differences among the constituent elements will be expected to favor an amorphous structure in preference [20] to a crystalline structure, due to the ability of the former structure to release the total strain energy, although some bonding energy is sacrificed as a result of its reduced coordination number. These factors have led to the formation of nanoscale or amorphous structures in a number of HEA systems that have been produced either by bulk casting or by deposition techniques [8,10].…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The sluggish diffusion is also far more pronounced with such a high number of elements, especially at a low deposition temperature, due to the confusion principle [22] and the increased packing density [23]. Finally, the large atomic size differences among the constituent elements will be expected to favor an amorphous structure in preference [20] to a crystalline structure, due to the ability of the former structure to release the total strain energy, although some bonding energy is sacrificed as a result of its reduced coordination number. These factors have led to the formation of nanoscale or amorphous structures in a number of HEA systems that have been produced either by bulk casting or by deposition techniques [8,10].…”
Section: Resultsmentioning
confidence: 95%
“…Comparison of the maximum working temperature between the present work and other barrier research published recently[16][17][18][19][20] …”
mentioning
confidence: 72%
“…At annealing temperatures above 700°C the TaC becomes predominant (Fig. 4) and, probably, some additional stable Ta-C and may be Ta-O compounds can form [37]. Ferro had discussed the interaction between hot filament and deposited gas [38].…”
Section: Resultsmentioning
confidence: 97%
“…12 However, the resistivity of as-deposited Ru 77 Ta 15 C 7 in this study is 143 lX cm, while that of 900°C-annealed film is as low as 20 lX cm. Laurila et al 13 showed that the resistivity of Ta 53 C 47 is 210 lX cm, and 7-nm-thick TaC fails at 550°C for 30 min. For the ternary ruthenium nitride, the 15-nm-thick Ru-Ta-N on SiO 2 /Si substrate fails at 900°C for 30 min; however, no related resistivity result has been shown.…”
Section: Compositions and Electrical Resistivity Of The Fabricated Rumentioning
confidence: 99%